TRIM44 promotes proliferation and metastasis in non-small cell lung cancer via mTOR signaling pathway - Xing, Ying (Oncotarget, 2016)
Tripartite motif-containing protein 44 (TRIM44) was recently identified as a potential therapeutic target in several types of malignancy, but its effect on the clinical course of malignancy and its underlying regulatory mechanism remain largely unknown. The present study shows that upregulation of TRIM44 is associated with poor differentiation, advanced pTNM stage, adenocarcinoma subtype, lymph node metastasis and, most importantly, unfavorable survival in patients with non-small cell lung cancer (NSCLC). TRIM44 knockdown inhibited the invasion and migration of human NSCLC cells, which was concurrent with downregulation of mesenchymal markers and upregulation of epithelial markers. Overexpression of TRIM44 induced the epithelial-to-mesenchymal transition (EMT) and increased the metastatic potential of lung cancer cells. Additionally, TRIM44 induced cell proliferation in vitro and tumor growth in vivo by accelerating G1/S transition via upregulation of cyclins and CDKs. TRIM44-induced mTOR signaling, EMT, and cyclin/CDK upregulation were reversed by treatment with a mammalian target of rapamycin (mTOR) inhibitor. These results provide a model for the relationship between TRIM44 expression and lung cancer progression, and open up new avenues for the prognosis and therapy of lung cancer.